CONSUMER DECISION MAKING OF FEMININE SANITARY PRODUCTS IN MANADO - Matheos, Anggun N.; Pangemanan, Sifrid S.; Pandowo, Merinda (Universitas Sam Ratulangi, 2017)
Abstract: The development of the business world in the era of globalization is going rapidly, which contributes in economic growth nationwide. In line with it makes the better level of income and the buying power the community grew to meet the need and desire of the will goods or services. The purpose in this study is to identify of consumer decision making of feminine sanitary product in Manado. Decision making is one of the most important function of the managers in any kind of organization. Among difference managers’ decision strategic decision – making is a complex process that must be understood completely before it can be practiced effectively. Qualitative research is a broad methodological approach that en compasses many research method. Base on the data that collected 11 from 19 informant using product Charm as their feminine sanitary product. Most of them like to try another product but keep choose the older one. They choose what they feel comfortable to use. The manufacturer are paying more attention to the desires of the consumer so that the consumer be loyal to one brand, in other words the need for differentiation of products with a wide range of functional and usability needed by consumers. Keyword: consumer decision making, consumer behavior, feminine sanitary product